OPTIMALISASI KINERJA: RENCANA DAN PROGRES REFORMASI BIROKRASI KEMENTERIAN PERHUBUNGAN - Arief Prayitno (Universitas Jenderal Ahmad Yani, 2024)
Bureaucratic reform has become an important agenda in efforts to improve the performance and effectiveness of government institutions in various countries, including Indonesia. The Ministry of Transportation (Kemenhub) has been actively carrying out various organizational transformation efforts to improve its performance and responsiveness to community needs since 2010. This reform process is based on the theory of organizational change, which emphasizes the importance of commitment from all parties involved, support from organizational leadership, and change that carried out gradually and measurably. Analysis of the implementation of bureaucratic reform at the Ministry of Transportation shows that the steps taken have provided positive results in improving operational efficiency and service quality in the transportation sector. Commitment from all levels of employees, led by visionary leaders, is the key to success in implementing these changes. However, there are still several challenges that need to be overcome in continuing bureaucratic reform at the Ministry of Transportation. Effective and efficient budget management remains a major concern, and a clear understanding of the benefits of bureaucratic reform needs to be disseminated more widely. Open and ongoing communication with stakeholders is essential to ensure continued support for the changes being made. By strengthening commitment, developing human resources, and using information technology more effectively, the Ministry of Transportation can continue to improve its performance and services for the community in a continuously developing transportation context.